2011
DOI: 10.5480/1536-5026-32.1.22
|View full text |Cite
|
Sign up to set email alerts
|

PREPARINGtheNurse ScientistforACADEMIA and INDUSTRY

Abstract: The number of doctoral programs in nursing has been increasing. However, these programs tend to focus on preparing nurse scientists to conduct research, and many spend little time preparing doctoral students for the educator, clinical researcher, or administrator role. Leaders of doctoral programs have identified the need to prepare doctoral students in the functional roles they will assume upon graduation, in addition to the researcher role. This article describes a two-course (six-credit) sequence of courses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…The participants' comments on the shortage of eligible faculty to teach in doctoral programs are congruent with other reports indicating that worldwide faculty shortage is a key issue facing doctoral programs in nursing (Jackson et al, 2011;Lewallen & Kohlenberg, 2011). The university in the current study addressed this faculty issue by announcing the program as a national program structured within a global context where national and international experiences merged.…”
Section: Facultysupporting
confidence: 87%
See 3 more Smart Citations
“…The participants' comments on the shortage of eligible faculty to teach in doctoral programs are congruent with other reports indicating that worldwide faculty shortage is a key issue facing doctoral programs in nursing (Jackson et al, 2011;Lewallen & Kohlenberg, 2011). The university in the current study addressed this faculty issue by announcing the program as a national program structured within a global context where national and international experiences merged.…”
Section: Facultysupporting
confidence: 87%
“…They reported active involvement in research, publications, presentations, and professional leadership which enhanced their sense of accomplishment as scholars. All study participants are currently employed in academia, agreeing with the literature citing that while nursing doctoral program graduates embark on diverse career paths, the majority of doctoral graduates are employed in academic institutions (Lewallen & Kohlenberg, 2011;Sakalys et al, 2001). Doctorally qualified nurses are needed globally to meet workforce demands and ensuring a sustainable academic workforce (Berlin & Sechrist, 2002;Potempa, Redman & Landstrom, 2009).…”
Section: Administrationmentioning
confidence: 94%
See 2 more Smart Citations
“…Some graduate students may have graduate assistant positions that expose them to clinical teaching, while others may have opportunities to become research assistants. Leaders of doctoral programs acknowledge the need to prepare graduates for more than the research scientist role (Lewallen & Kohlenberg, 2011). Kelly (2002) found that graduates of doctoral programs seek research careers because they feel inadequately prepared for a teaching role in academia.…”
Section: Role Transition Role Strain and Organizational Culturementioning
confidence: 99%